Avaliação da qualidade de vida de agricultores no estado da Paraíba - Vieira, Jadcely Rodrigues (2008)
This research aims to evaluate the quality of life of families living in the countryside. The quality of life is understood in this work in two dimensions: the objective dimension that can be understood as access to income, food, safety, housing, schooling, physical health, etc., and the defined subjective dimension As responses of individuals to the various dimensions of life, be they objective, as income, education, food, and emotional when it concerns satisfaction with life and living conditions. To achieve the goals proposed in this study, two instruments were used: WHOQOL-bref (WHOQOL-bref) and a questionnaire on Quality of Life Objective. The sample consisted of 293 participants, 51% female and 49% male. The results showed that males show greater satisfaction with the various domains than females and that satisfaction with psychological health has to do with variables such as gender, age, disposition to work, good physical health and having Satisfaction with the various domains of life. Regarding the general evaluation of the quality of life, 77.8% gave scores between 6 and 10 for quality of life, 16.4% scored 5 and 5.8% gave scores between 1 and 4 for the life they lead in the field .